The Legacy of the Habsburg Empire in the Constitutional Traditions of Successor States - Szabó, István (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
The states established in the territory of the former Austro-Hungarian Monarchy after World War I opened a new chapter in the history of the region. However, the problems arising from the heterogeneous ethnic composition remained the same as before 1918. The question was: can a state organization be formed in which all nations can preserve their own identity? This was also the main goal of the Habsburg Empire after the “spring of the peoples” of 1848. The study reviews the reform efforts of these 70 years, and what particular steps and reform plans were taken after 1848 to resolve ethnic tensions. The most important issue was to establish the internal division of the empire, along historical or ethnic boundaries. The starting point was how historical boundaries could be transformed into ethnic ones. The nations of the empire may agree with each other, but if they do not, the ruler must make that decision. This formed the second essential question: is the reform of the empire based on popular sovereignty or monarchical legitimacy? The third problem was the model of state organization formed by the interior of the empire. They should either form a loose federation of states, or a federal state with a closer relationship. The most significant reform implemented was the 1867 Compromise, which followed historical boundaries, rested on the principle of popular sovereignty, and created a loose state union. However, many nations of the empire were dissatisfied with this. Subsequent internal reforms (the Croatian compromise on the Hungarian side and the Moravian or Galician compromise on the Austrian side) could not solve this properly either.KEYWORDS: historical boundaries, ethnic boundaries, popular sovereignty, monarchical legitimacy, federal states, federation of states, compromise.